Development of portable charger for mobile phone using arduino microcontroller during disaster recovery - Gunawan, Teddy Surya; Kartiwi, Mira; Suhaimi, Nur Hanis Sabrina; Abu Bakar, Rashidah (2013)

(untitled)
In the recent years, hundreds to thousands of people have been killed in many disasters across Asian region, such as tsunami, floods, earthquakes and so on. During disaster, most of the electricity supply will be disrupted, then the telecommunication networks will fail. During emergency response, the necessity to have portable charger for mobile phone arises as the victim could communicate with the relevant authorities or volunteers. The objective of this research is to design and develop portable charger for mobile phone using Arduino microcontroller, which can be used effectively during disaster event. Three main circuits have been implemented, including energy harvesting and DC/DC boost converter, intermediate battery charging, and Li-Ion charging. The energy harvester circuit will be the combination of mechanical and solar panel. Performance evaluation have been conducted to evaluate the best DC motor and solar panel, as well as the final charging time for Li-Ion battery.